Penerapan Soft System Methodology (SSM) dan PIECES dalam Peningkatan Pelayanan Klinik Hewan - Feru Adiningrat; Nuri Rofi Attien; Amanda (ALMUISY: Journal of Al Muslim Information System, 2026)
Effective and efficient veterinary clinic services play an important role in supporting animal welfare and preventing zoonotic disease risks. However, many small and medium-scale veterinary clinics in Indonesia still face problems such as manual medical record management, long service queues, and the lack of integrated information systems. This study aims to analyze service-related problems and design a web-based veterinary clinic information system using a mixed methods approach with a sequential explanatory design through the integration of Soft System Methodology (SSM) and the PIECES framework. The quantitative approach serves as the primary method to evaluate system performance based on measurable indicators, including service time and system performance tested using Apache JMeter, while the qualitative approach supports contextual analysis of organizational problems and user requirements through SSM stages. The results indicate that the proposed system reduced registration waiting time by approximately 80%, accelerated medical record retrieval from 3–5 minutes to less than 3 seconds, and demonstrated stable system performance with a 0% error rate during concurrent user load testing. This study concludes that integrating SSM and PIECES within a mixed methods framework is effective for the development and evaluation of information systems in small to medium-scale veterinary clinics.